2016
DOI: 10.3390/sym9010005
|View full text |Cite
|
Sign up to set email alerts
|

Some Algebraic Polynomials and Topological Indices of Generalized Prism and Toroidal Polyhex Networks

Abstract: Abstract:A topological index of graph G is a numerical parameter related to G, which characterizes its topology and is preserved under isomorphism of graphs. Properties of the chemical compounds and topological indices are correlated. In this report, we compute closed forms of first Zagreb, second Zagreb, and forgotten polynomials of generalized prism and toroidal polyhex networks. We also compute hyper-Zagreb index, first multiple Zagreb index, second multiple Zagreb index, and forgotten index of these networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…For estimating the alkanes boiling point, wiener suggested wiener index firstly in 1947. M polynomial also played the identical occupation in driving the secure structure of numberless degree based topological indices (Ajmal et al, 2016;Kulli, 2016;Klavžar and Gutman, 1996). Consequently, in Table 1, explicit expressions for some continuous degree based Topological indices are listed in Table 1.…”
Section: M-polynomialmentioning
confidence: 99%
“…For estimating the alkanes boiling point, wiener suggested wiener index firstly in 1947. M polynomial also played the identical occupation in driving the secure structure of numberless degree based topological indices (Ajmal et al, 2016;Kulli, 2016;Klavžar and Gutman, 1996). Consequently, in Table 1, explicit expressions for some continuous degree based Topological indices are listed in Table 1.…”
Section: M-polynomialmentioning
confidence: 99%
“…We are interested in the study of irregularity determinants of some famous dendrimers, namely, nanostar dendrimer D[p], fullerene dendrimer NS 4 [p], and polymer dendrimer NS 5 [p]. It has been keenly observed that the geometry and pattern of chemical systems characterize its physical aspects [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Graph labeling has been used in many applications such as coding theory, X-ray crystallography, radar, astronomy, circuit design, communication network addressing, and data base management [10][11][12]. In the present article, we have studied super T (4,2) -antimagic labeling of web graphs W(2, n) for differences d ∈ 0, 1, .…”
Section: Introductionmentioning
confidence: 99%